STRATIFIKASI SOSIAL DALAM PERKAWINAN MASYARAKAT ISLAM SASAK (Studi Pada Perkawinan Masyarakat Desa Sengkerang, Lombok Tengah) - Siti Aminah (Jurnal Sosiologi Agama, 2017)
Social stratification and caste, in Sengkerang Village of Central Lombok, woman who has a high social class and caste gets high dowry from the bridegroom. This research is qualitative research with the descriptive-analytic approach. Technique of collecting data is used by the various methods—observation, interview and documentation method. Primary data resource is earned from the result of interview and observation to the village chief of Balin Gagak in Sengkerang, religious leaders and public figure, while the secondary data resource is earned form the literatures. Analyzing data is done by three steps; reduction of data, displaying data and verification of data. This research uses capitalist theory and social-functional stratification. The result of this research shows a marriage in Sasak Islamic community has three various marriages—homogami, hipogami, and hipergami and social stratification in the marriage of Sasak Islamic community appears because of being a higher and lower social stratification, which is determined by education, power, caste, affluence, respectability, and other causes. The caste is a main factor giving most influence to determine a social stratification of Sasak Islamic Community. So the higher her aristocracy is, the higher her title or her dowry is. Aristocrats are called mamiq by their children and jajarkarang is called amaq by their children. And the children of aristocrat earn a title; lalu, raden, or denda and the children of jajarkarang do not earn a title.